Identification of FimH derivatives as adjuvant vaccinated with PAc that enhance protection against Streptcoccus mutans colonization. (June 2019) - Liu, Zhongfang; Chen, Junlan; Li, Wuyou; Bi, Yongli; Li, Yuhong; Fan, Mingwen
Abstract: FimH is the adhesin of type I fimbriae expressed on Escherichia coli that can mediate specific adherence to host cells. High binding mutations in FimH are related to the adaptive evolution of bacteria. However, additional roles that these allelic variations may play remain elusive. To investigate novel biological functions of the mutations in FimH, we introduced four different variants of FimH by incorporating single amino acid substitutions at specific sites, namely A25P, G73R, A106, and T158P, respectively. In this study, adjuvant potential of FimH variants was evaluated by investigating their ability to trigger innate immune response to DC2.4 and adaptive immunity to improve immunological characteristics. The data revealed that purified A106 and T158P up-regulated the expression of co-stimulatory molecules critically involved in DC2.4 activation by interaction with TLR4, whereas A25P and G73R did not induce the phenotypic maturation of DC2.4. Besides, the culture of DC2.4 with A106 and T158P enhanced the release of cytokines and protein phagocytosis. When formulated with PAc, T158P elicited more robust PAc-specific IgG and IgA antibody responses compared to PBS, PAc and PAc+K12 groups and inhibited bacteria colonization. Collectively, the results confirmed that the T158P mutation located around the inter-domain interface of the protein induced a specific enhancement effect on adjuvant characteristics. Highlights: FimH variants induce the activation of DC2.4 by interaction with TLR4. FimH variants increase the release of cytokines and protein phagocytosis by DC2.4. FimH variants plus PAc elicit systemic and local PAc-specific antibodies response. FimH variants formulated with PAc inhibit the colonization of S. mutans.